Hubungan Peranan dari Utilitarianisme Terhadap Kinerja Karyawan di Bidang Perhotelan - Jesslyn Natania; Felicia Clarisa Wijaya; Nurul Stephanie; Davina Artemesia Thonora (IPM2KPE, 2023)
This research aims to determine the relationship between the role of Utilitarianism on Employee Performance in the Hospitality sector. The sampling method used was